Ethnobotanical studies of plants utilization in the gold mining region in Central Kapuas, Indonesia - SITI SUNARIYATI (Biodiversitas Journal of Biological Diversity, 2018)
Sunariyati S. 2018. Ethnobotanical studies of plants utilization in the gold mining region in Central Kapuas, Indonesia. Biodiversitas 19: 215-221. Studying on ethnobotany is intended to expand the knowledge of interaction between human and plants. There are various uses of plants such as in food industry, medicine, and evidently in gold mining activity. Some gold miners believe that specific plants could be used as indicators for the presence of gold metal beneath the area the plants grown. The objective of this research were to (i) learn the ethnobotanical knowledge of Dayak Ngaju people in Central Kapuas, Central Kalimantan, Indonesia gold-mining areas, (ii) identify some species of plants used by local miners as indicators for the presence of gold metal underneath. The research consisted of two phases. The first phase was a qualitative approach, using in-depth interviews and identification of plant species used for gold metal indicators. The second phase was the quantitative approaches analyzing the ethnobotanical knowledge of Dayak Ngaju people in Central Kapuas (Indonesia) gold-mining areas. The results showed that the people of Dayak Ngaju in Central Kapuas had local knowledge about the use of plants for food industry, medicine, and also in gold mining activity. At least 10 (ten) plant species were believed to be indicators for the presence of gold metal. Based on the Fidelity level (FL) and the Relative Used-Value (RUV), katune (Agrostistachys sessilifolia (Kurz) Pax & Hoffm) is the most plant served the purpose as indicators for the presence of gold metal.